Understanding the Parental Stress Scale With a Foster Carer Cohort. Issue 4 (11th August 2020) - Harding, Leith; Murray, Kate; Shakespeare‐Finch, Jane; Frey, Ron
Abstract : Objective: Using a cohort of foster and kin carers, the research examined the underlying factor structure of the Parental Stress Scale (PSS; Berry & Jones, 1995). A hypothesized underlying two‐dimensional theoretical model was explored. Background: With the growing demands on the foster care system, including poor retention and recruitment of foster carers, there is an urgent need to explore the positive and negative factors that may influence carers continued engagement in the role. Method: The factor structure of the PSS was examined in a sample of foster and kin carers in Australia ( N  = 324). The PSS consists of 10 statements addressing stressful aspects of parenting and eight statements addressing satisfying aspects of parenting. Exploratory factor analysis (EFA) explored the underlying theoretical structure of the scale as determined by the developers. Confirmatory factor analysis (CFA) was used to confirm whether four factors would sustain reduction to a two‐dimensional (satisfaction–stress) model. Results: EFA and CFA supported a two‐dimensional moderately correlated model measuring parent stress and parent satisfaction. The Parent Stress Index IV Short Form provided concurrent validity for the PSS stress subscale and previous analyses have also identified the strength of these dimensions over time, cohorts, and contexts. Conclusion: The current study supports using the subscale scores in research with foster carers and potentially other populations to better capture both stress and rewards and satisfaction related to their parenting role. Implications: Application of the PSS subscales can assess interactions or moderating effects of parenting in specific cohorts, making the PSS a valuable instrument to examine the balance between stress and reward for parents, foster parents and others who are "parenting" children.